Age, time orientation and risk perception are major determinants of discretionary salt usage. (1st April 2022) - Antúnez, Lucía; Vidal, Leticia; Giménez, Ana; Curutchet, María Rosa; Ares, Gastón
Abstract: The present work explored the relationship between discretionary salt usage and personal characteristics, using boosted regression trees (BRT). Specifically, the focus was on how socio-demographic characteristics and personality traits linked to risk perception and time orientation impact on discretionary salt consumption patterns. For this purpose, an online cross-sectional survey with a convenience sample of 498 Uruguayan participants was carried out. Participants completed the consideration of future consequences (CFC) scale adapted for eating behaviour, a short survey about discretionary salt consumption patterns and indicated their degree of agreement with statements measuring perceived risk of sodium consumption. Finally, socio-demographic data were collected. BRT were applied to build predictive models that related discretionary salt usage to socio-demographic characteristics, the two factors of the CFC-Food scale (consideration of the future and consideration of the immediate consequences of eating behaviour), and the two factors of the perceived risk of sodium consumption scale (severity of perceived risks and risk compensation). Age, time orientation and perceived risk were the most relevant explanatory variables for discretionary salt usage. Older people had a lower likelihood of adding salt to food, either at home or when eating out. In addition, individuals who tend to be present rather than future oriented, as well as those with low perception of risk severity and susceptibility were more likely to add salt to foods. Results from the present work suggest that communication campaigns to reduce discretionary salt intake should mainly focus on stressing the short-term health benefits of reducing sodium intake and raising perceived susceptibility. Highlights: The relationship between discretionary salt consumption and individual characteristics was explored. Boosted regression trees were used to predict discretionary salt consumption. Age, time orientation and perceived risk determine discretionary salt consumption. Older people had a lower likelihood of adding salt to food. Present-oriented individuals and those with low risk perception were more likely to add salt to foods.